2014
DOI: 10.1002/jhm.2226
|View full text |Cite
|
Sign up to set email alerts
|

Assessing preventability in the quest to reduce hospital readmissions

Abstract: Hospitals devote significant human and capital resources to eliminate hospital readmissions, prompted most recently by the Centers for Medicare and Medicaid Services (CMS) financial penalties for higher-than-expected readmission rates. Implicit in these efforts are assumptions that a significant proportion of readmissions are preventable, and preventable readmissions can be identified. Yet, no consensus exists in the literature regarding methods to determine which readmissions are reasonably preventable. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Each year, hospital readmissions affect 18.2% of Medicare beneficiaries (1) and cost Medicare between $15 and $17 billion (2). Effective October 1, 2012, Section 3025 of the Patient Protection and Affordable Care Act established the Hospital Readmissions Reduction Program, authorizing the Centers for Medicare and Medicaid Services to impose financial penalties on hospitals for excessive readmissions within 30 days of hospital discharge (3).…”
Section: Introductionmentioning
confidence: 99%
“…Each year, hospital readmissions affect 18.2% of Medicare beneficiaries (1) and cost Medicare between $15 and $17 billion (2). Effective October 1, 2012, Section 3025 of the Patient Protection and Affordable Care Act established the Hospital Readmissions Reduction Program, authorizing the Centers for Medicare and Medicaid Services to impose financial penalties on hospitals for excessive readmissions within 30 days of hospital discharge (3).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of septic shock survivors that focused on the cause of readmission, Ortego and colleagues found that 46% of 30-day readmissions were infection-related, including new, unresolved, and recurrent infections (17). Investigation is required to determine whether sepsis itself and/or the care provisions required to treat the acute illness (e.g., catheter-associated infections, transfusions [40]) confer increased readmission risk that may be preventable (41).…”
Section: Discussionmentioning
confidence: 99%
“…5 -11 A common criticism of using readmission rates as a health care quality measure is that many readmissions are not causally related to the hospital care provided during the index admission; rather, they may represent worsening of underlying chronic disease. 12,13 In addition, some argue that hospitals should not be held accountable for readmissions because factors that contribute to readmissions often are not hospital factors (eg, postoperative complication) but instead are outpatient (eg, nurse unable to visit home) or patient (eg, not taking prescribed medications) factors and thus beyond the hospital's direct control. 14,15 Currently, 3 main strategies for ascertaining the potential preventability of hospital readmissions include the following: claims-based algorithms, medical record review, and structured interviews.…”
mentioning
confidence: 99%